Analysis of the Preparation of Financial Statements for Al-Amin Mosque, Karella Village, Mare District, Bone Regency Based on PSAK 45 - Hasriani; Rini Idayanti; Hartas Hasbi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2026)
This research aims to understand the preparation of financial statements for Al-Amin Mosque in Karella Village, Mare District, Bone Regency based on PSAK 45, as well as to identify the obstacles faced by the mosque management in preparing financial statements according to these standards and the efforts made to overcome them. This research uses a field research type with a descriptive qualitative approach. Data were obtained thru observation, interviews, and documentation conducted with the mosque administrators, particularly those involved in the mosque's financial management. The research results show that the preparation of financial reports for Al-Amin Mosque in Karella Village, Mare District, Bone Regency is still done simply with a cash in and cash out recording system. The financial statements prepared do not fully comply with PSAK 45 regulations because they do not yet include the statement of financial position, statement of activities, statement of cash flows, and notes to the financial statements in their entirety. The main obstacles faced by the mosque management include limited understanding of accounting and PSAK 45, lack of training, and the absence of an adequate recording system. The efforts that can be made to overcome these obstacles include enhancing the understanding of the management thru training, mentoring, and the development of a simple and easy-to-implement financial recording system. With the implementation of PSAK 45, it is hoped that the financial management of the mosque will become more transparent, accountable, and can increase the trust of the congregation and the community.